Effectiveness of simultaneous manipulation by the upper and lower limbs in a planar 2-DOF reaching task - Masaharu KOMORI; Yukihiko MAMIYA; Yuki WATABE; Tatsuro TERAKAWA; Michio NOMURA (Mechanical Engineering Journal)
A person capable of using more than one of four limbs simultaneously for manipulation can also be expected to be capable of performing concurrent and complex tasks and improving work efficiency. However, to our knowledge, no studies have investigated simultaneous tasks that require multi-degree-of-freedom manipulation, particularly those in which the lower limb engages in the same task as the upper limb. In this study, we developed a system to evaluate work performance and subjective mental workload using reaching movements with multiple limbs. To foster comparisons among various manipulations, experiments were conducted with single manipulation by a hand or a foot, simultaneous manipulation by the homologous limbs (left-hand_right-hand, left-foot_right-foot), simultaneous manipulation by the ipsilateral heterologous limbs (left-hand_left-foot, right-hand_right-foot), and simultaneous manipulation by the contralateral heterologous limbs (left-hand_right-foot, right-hand_left-foot). The processing time and accuracy of each limb were lower during two-than one-limb manipulation. In other words, a bilateral deficit tended to be seen. When manipulating with two limbs, manipulation with the homologous limbs was significantly superior to that with the heterologous limbs in terms of processing time, accuracy, and mental workload. Because the work performance of a foot tended to be worse than that of a hand in the one-limb manipulation, the work performance of the two-limb manipulation using both feet was expected to be the worst in the two-limb manipulations. However, the experimental results showed that the work performance of the heterologous limbs was worse than that of both feet. Manipulation with the contralateral heterologous limbs tended to be superior to that with the ipsilateral heterologous limbs in terms of processing time, accuracy, and mental workload. Regarding two-limb manipulation, the homologous limbs tended to perform best, followed by the contralateral and ipsilateral heterologous limbs.